Supportive Communication of Volunteer Toward Cancer Patients at Rumah Pejuang Kanker Ambu Bandung - Putri Aji, Maulidya; Suciati, Suciati (Jogjakarta Communication Conference (JCC), 2023)
The process of healing cancer will be more effective if the patient gets support and motivation from theirselves and the environment. Therefore, this research was conducted to get an overview and form of how supportive communication is carried out by volunteers with cancer patients at Rumah Pejuang Kanker Ambu Bandung. The method used in this research is qualitative descriptive research. The informants in this study used a purposive sampling technique with data collection techniques used in-depth interviews and observation. The result shows that volunteers at RPKA have implemented six indicators of supportive communication for cancer patients: more concerned with what will be conveyed than assessing the person first, communicate well and talk about everything without any coercion, be honest about various patient conditions in certain ways, pay attention to the condition of each patient, embrace and not limit closeness with patients, also receive advice for better personal and performance towards patients. Communication made by volunteers has succeeded in making patients enthusiastic about carrying out daily activities and treatment, being able to think positively, accepting circumstances, and helping patients have the confidence to recover.